1,7-Diaminoheptane N-D4 - M. P. M. Marques, Universidade de Coimbra, Portugal (My University, 2002)
Inelastic Neutron Scattering spectrum of 1,7-Diaminoheptane N-D4, H₂N-(CH₂)n-NH₂ n=heptane, measured on the TOSCA instrument.
Keywords: TOSCA